Biblical interpretation in the era of the Reformation essays presented to David C. Steinmetz in honour of his sixtieth birthday. - Muller, Richard Alfred, 1948-; Thompson, John L. (Grand Rapids, MI Eerdmans, 1996)
Includes bibliographical references.
Keywords: Steinmetz, David Curtis; Bible -- criticism, interpretaton, etc. -- history -- 16th century